2021
DOI: 10.1007/s11191-021-00251-w
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions, Knowledge, and Attitudes Towards the Phenomenon of Radioactivity

Abstract: The teaching of the phenomenon of radioactivity is considered a key ingredient in the path towards developing critical thinking skills in many secondary science education curricula. Despite being one of the basic concepts in general physics courses, the scientific teaching literature of the last 40 years reports a great deal of misconceptions and conceptual errors related to radioactivity that seemingly appear regardless of the educational level and context. This study reports the first cross-sectional diagnos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several studies (Morales López & Tuzón Marco, 2022;Nakiboglu & Tekin, 2006;Wadana & Maison, 2019) indicate that electromagnetic radiation is a complex and challenging phenomenon for students to comprehend. Although educational programs cover topics related to electromagnetic radiation throughout all years of education, research has shown that teachers have limited knowledge in this area, as evidenced by their low scores on basic questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Morales López & Tuzón Marco, 2022;Nakiboglu & Tekin, 2006;Wadana & Maison, 2019) indicate that electromagnetic radiation is a complex and challenging phenomenon for students to comprehend. Although educational programs cover topics related to electromagnetic radiation throughout all years of education, research has shown that teachers have limited knowledge in this area, as evidenced by their low scores on basic questions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these concepts are regarded as some of the most challenging and abstract ones to grasp (Siersma et al, 2021;Ye et al, 2010), the quantity of research devoted to them is noticeably lower compared to the aforementioned concepts in physics (Morales López & Tuzón Marco, 2022;Plotz, 2016).…”
Section: Open Accessmentioning
confidence: 99%
“…Discussions arise during various events that could affect a nuclear power plant, e.g. accident at the Fukushima-Daiichi nuclear power plant in 2011, anniversaries of the Chernobyl accident in 1986, earthquake near the Krško nuclear power plant in Slovenia in 2020, discussions about the second unit of the Krško nuclear power plant in 2021 and 2022... Nuclear accidents and the effects of ionizing radiation on living beings and inanimate nature are topics of great interest for students [10].…”
Section: Introductionmentioning
confidence: 99%